ANALISIS INTERAKSI TANAH-STRUKTUR DENGAN METODE ELEMEN HINGGA UNTUK MENENTUKAN DISTRIBUSI TEKANAN TANAH LATERAL DINAMIS PADA DINDING BASEMENT - Sumiartha, Putu
Most currently available methods to analyze seismic lateral load distribution for rigid retaining walls were developed under assumptions that the walls are presumed to be fixed-base. For basement wall, bottom of basement is not actually fixed-base. Under seismic loading, soil and basement wall would experience relative movement due to presence sal/-structure effect. In this study, soil-structure interaction FE analysis to derive seismic design lateral load distributions for basement wall is studied. Two-dimensional FE computer program FLUSH that approximate the 3-dimensional nature of the problem was used in the analysis in frequency domain. The analysis was verified with time domain PLAXIS Dynamics program. The analysis was performed considering variation in soil conditions, level of base-rock accelerations, frequency content of input motions, depth of basement; and depth of base-ruck. Variations in soil conditions are represented by soil classification based on average shear wave velocity of the soil layer referring to UBC97. Result of the analysis indicated that, in general, the distributions of lateral load tends to reach maximum around surface of basement depth and tend to decrease up to bottom of the basement at about two-fifth of maximum value. Recommendation of seismic lateral load distribution considering to soil condition and PBA are provided for input to seismic building code for basement wall.